Analisis Kurikulum ISMUBA (Al-Islam, Kemuhammadiyahan, dan Bahasa Arab) Perspektif Kurikulum Merdeka - 'Ainun Na'iim, Muhammad; Ardiansyah, Adnan (Kartika: Jurnal Studi Keislaman, 2025)
The ISMUBA curriculum is a development of the PAI curriculum in schools combined with Muhammadiyah social organizations. The presence of an independent curriculum is the main basis for the implementation of education in all existing educational institutions. This study aims to determine the relevance of the basic ISMUBA curriculum development concept to the main foundation of the independent curriculum contained in the Pancasila Student Profile. This type of research is library research, the data collected in this study are two types of data, namely primary data and secondary data. The data collection technique used by this researcher is a literature study. The data analysis technique in this study used qualitative analysis techniques in a deductive way. The research results obtained that the subject matter of the independent curriculum contained in the Pancasila Student Profile has relevance to the ISMUBA curriculum which includes three dimensions. The first dimension has the dimensions of Faith, Fear of God Almighty, and Noble Morals. The second dimension is the dimension of Global Diversity. The third dimension is the cooperative dimension. From these three dimensions, the objectives of the ISMUBA curriculum graduates and the Pancasila student profile are based.